Concept of Intention in Educational Organisation - Hamat, Wan Hasmah Laili Wan; Hamzah, Mohd Isa; Zulkifli, Hafizhah (International Journal of Psychosocial Rehabilitation, 2020)
Intention is the foundation of one’s doing, practice, behaviour and attitude. Intention to do something for the sake of seeking Allah’s blessings is considered as ibadah meanwhile doing things for reward, materialistic and worldly purpose is insignificant. A righteous intention is manifested through sincere actions, good practice, perseverance, determination and strong will. Thus, this conceptual paper seeks to determine the concept of intention that educational organisation should adhere to including among pre-service teachers. This article aims to analyse literature focusing on the conceptualization of intention. Content analysis denotes that intention functions as an internal catalyst in enforcing individual’s motivation in everyday life which leads to quality output and productivity. Based on this conceptualization of intention, spiritual element hence should be implemented in educational organization. This is because education is the thrust in nation building involving all parties from the policy makers down to the executors. Intention is not only a requirement in etiquette but in fact is a salient principle in working culture of Islam as righteous intention enables the attainment of educational philosophy, mission, vision and objectives of organization.